MONOTEISME DAN KEKERASAN TERHADAP “YANG LAIN” - Sunarko, A. (Faculty of Philosophy, Parahyangan Catholic University, Bandung, 2007)
It is often claimed that violence goes hand in hand with monotheistic religions. While the facts of it is undeniable, this article seeks to argue that there is no inherent correlation between the two. On the contrary, monotheism has proved to bear the liberative and emancipatory power. It has also paved the way towards universal ethics. It is true, however, that the structure of monotheistic religion oftentimes leads to the need for selfdefinition, which in turn, may result in ostracizing the 'other'. One of the tasks of theology is precisely to constantly remind the people of tacit interests and exessive need for self-definition.